Differential expression of postsynaptic NMDA and AMPA receptor subunits in the hippocampus and prefrontal cortex of the flinders sensitive line rat model of depression. Issue 11 (21st June 2016) - Treccani, Giulia; Gaarn du Jardin, Kristian; Wegener, Gregers; Müller, Heidi Kaastrup
Abstract: Glutamatergic abnormalities have recently been implicated in the pathophysiology of depression, and the ionotropic glutamate receptors in particular have been suggested as possible underlying molecular determinants. The Flinders Sensitive Line (FSL) rats constitute a validated model of depression with dysfunctional regulation of glutamate transmission relatively to their control strain Flinders Resistant Line (FRL). To gain insight into how signaling through glutamate receptors may be altered in the FSL rats, we investigated the expression and phosphorylation of AMPA and NMDA receptor subunits in an enriched postsynaptic fraction of the hippocampus and prefrontal cortex. Compared to the hippocampal postsynaptic fractions of FRL rats, FSL rats exhibited decreased and increased levels of the NMDA receptor subunits GluN2A and GluN2B, respectively, causing a lower ratio of GluN2A/GluN2B. The GluA2/GluA3 AMPA receptor subunit ratio was significantly decreased while the expression of the individual GluA1, GluA2, and GluA3 subunits were unaltered including phosphorylation levels of GluA1 at S831 and S845. There were no changes in the prefrontal cortex. These results support altered expression of postsynaptic glutamate receptors in the hippocampus of FSL rats, which may contribute to the depressive‐like phenotype of these rats. Abstract : Using a subcellular fractionation approach for purification of the Triton‐Insoluble postsynaptic Fraction (TIF), the authors show altered expression of NMDA receptor subunits in the hippocampus of the Flinders Sensitive Line rat model of depression. Altered composition of NMDA receptors may represent a critical component of the depressive‐like behaviors observed in this model.